2007
DOI: 10.1007/s11627-007-9053-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of methods for using polyethylene glycol as a non-permeating osmoticum for the induction of microspore embryogenesis in the Brassicaceae

Abstract: The objective of this work was to enhance the quality and quantity of microspore-derived embryos of cruciferous species by using polyethylene glycol (PEG) to replace sucrose in the culture medium. The main advantage in using PEG is that it produces embryos that are morphologically more similar to zygotic embryos and have enhanced germination capabilities. When microspores were cultured in full strength NLN medium supplemented with 25% (w/v) PEG, the addition of 3 ml of full strength NLN with 13% (w/v) sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…Prem et al (2008) reported a four-fold increase in B. juncea microspore embryogenesis when silver nitrate and activated charcoal were included in the culture medium. Other recent improvements include the addition of the anti-auxin, p-chlorophenoxyisobutyric acid (PCIB), to enhance microspore embryogenesis in B. juncea (Agarwal et al 2006), and substitution of polyethylene glycol for sucrose in B. nigra (L.) Koch, Crambe abyssinica Hochst., Raphanus oleifera L., and several genotypes of B. napus (Ferrie and Keller 2007). The B. napus microspore protocol has been successfully extended to another cruciferous species with the report by Leskovšek et al (2008) of DH plantlet production from rocket or arugula (Eruca sativa Mill.…”
Section: Cruciferous Speciesmentioning
confidence: 99%
“…Prem et al (2008) reported a four-fold increase in B. juncea microspore embryogenesis when silver nitrate and activated charcoal were included in the culture medium. Other recent improvements include the addition of the anti-auxin, p-chlorophenoxyisobutyric acid (PCIB), to enhance microspore embryogenesis in B. juncea (Agarwal et al 2006), and substitution of polyethylene glycol for sucrose in B. nigra (L.) Koch, Crambe abyssinica Hochst., Raphanus oleifera L., and several genotypes of B. napus (Ferrie and Keller 2007). The B. napus microspore protocol has been successfully extended to another cruciferous species with the report by Leskovšek et al (2008) of DH plantlet production from rocket or arugula (Eruca sativa Mill.…”
Section: Cruciferous Speciesmentioning
confidence: 99%
“…Osmotic pressure is correlated with plant development and differentiation, appropriate treatment by the common osmoticums such as sucrose, mannitol and polyethylene glycol (PEG) enhances the embryogenesis and organogenesis in Solanum melongena (Mukherjee et al,1991), Brassica napus (Ferrie & Keller, 2007) and white spruce (Picea glauca) (Misra et al, 1993).…”
Section: Chemical Additivesmentioning
confidence: 99%
“…Mapping genes related to microspore embryogenesis Tremendous differences among B. napus genotypes in their embryogenic response of cultured microspores have been reported (Ferrie 2003;Ferrie and Keller 2007). However, the genetic basis of the genotypic differences in microspore culture response remains largely unknown.…”
Section: Identification Of Genomic Regions and Genes Related To Micromentioning
confidence: 99%